A systematic review of interventions to enhance access to best practice primary health care for chronic disease management, prevention and episodic care - Comino Elizabeth; Davies Gawaine; Krastev Yordanka; Haas Marion; Christl Bettina; Furler John; Raymont Anthony; Harris Mark F (BMC, 2012)
Abstract Background Although primary health care (PHC) is a key component of all health care systems, services are not always readily available, accessible or affordable. This systematic review examines effective strategies to enhance access to best practice processes of PHC in three domains: chronic disease management, prevention and episodic care. Methods An extensive search of bibliographic data bases to identify peer and non-peer reviewed literature was undertaken. Identified papers were screened to identify and classify intervention studies that measured the impact of strategies (singly or in combination) on change in use or the reach of services in defined population groups (evaluated interventions). Results The search identified 3,148 citations of which 121 were intervention studies and 75 were evaluated interventions. Evaluated interventions were found in all three domains: prevention (n = 45), episodic care (n = 19), and chronic disease management (n = 11). They were undertaken in a number of countries including Australia (n = 25), USA (n = 25), and UK (n = 15). Study quality was ranked as high (31% of studies), medium (61%) and low (8%). The 75 evaluated interventions tested a range of strategies either singly (n = 46 studies) or as a combination of two (n = 20) or more strategies (n = 9). Strategies targeted both health providers and patients and were categorised to five groups: practice re-organisation (n = 43 studies), patient support (n = 29), provision of new services (n = 19), workforce development (n = 11), and financial incentives (n = 9). Strategies varied by domain, reflecting the complexity of care needs and processes. Of the 75 evaluated interventions, 55 reported positive findings with interventions using a combination of strategies more likely to report positive results. Conclusions This review suggests that multiple, linked strategies targeting different levels of the health care system are most likely to improve access to best practice PHC. The proposed changes in the structure of PHC in Australia may provide opportunities to investigate the factors that influence access to best practice PHC and to develop and implement effective, evidence based strategies to address these.